Efektivitas Peraturan Daerah Kota Kupang Nomor 7 Tahun 2013 Tentang Kesehatan Ibu, Bayi Baru Lahir dan Anak Balita di Wilayah Kerja Puskesmas Bakunase Kecamatan Kota Raja Kota Kupang - Yefri Jonathan Ae; Saryono Yohanes; Hernimus Ratu Udju (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study aims to find out and analyze the legal basis for considering the regulation of fine sanctions of Kupang Mayor Regulation Number 7 of 2013 concerning the health of mothers, infants and children under five and to find out and assess the effectiveness of the enforcement of Kupang Mayor Regulation Number 7 of 2013 concerning the Health of Mother, Infants and Children under five through the regulation of fine sanctions. This type of research is empirical normative research using interviews and data analysis methods that are carried out qualitatively. In this study, the author uses a type of empirical normative research or legal research that examines written law from the aspects of theory, history, philosophy, comparison, structure and composition, scope and material, general explanation of article by article, formality and binding force of a law but not binding aspects of its application or implementation. The results of the study show the legal basis for considering the regulation of fine sanctions in Kupang Mayor Regulation Number 7 of 2013 concerning the health of mothers, infants and children under five, because there are still incidents of childbirth outside health facilities in the working area of the Bakunase Health Center which can be at risk of maternal and infant mortality rates. This happens because there are still pregnant women who give birth at home because of impromptu childbirth so that childbirth does not occur in health facilities but outside health facilities or at home and childbirth is still helped by birth attendants. The risk of maternal and infant mortality can still occur. The effectiveness of the enforcement of Kupang Mayor Regulation Number 7 of 2013 concerning the Health of Mothers, Infants and Children Under Five through the regulation of fine sanctions in the working area of the Bakunase Health Center has been effective for health workers. For the public, there are still many who do not know about the Regulation of the Mayor of Kupang Number 7 of 2013 concerning the Health of Mothers, Babies and Children under five so that there are still incidents of childbirth outside health facilities and childbirth assisted by shamans. Knowledge about childbirth, attitudes and family support in this study also has an important role in determining mothers to have a safe delivery. It is suggested that new regional regulations need to be socialized to the community so that existing regulations can run effectively. An obedient society is also a basic thing so that regulations can run effectively.